The Genesis of Greek Intellectuality in Islamic and Western Historiographies of Science: A Comparative Overview - Mohd Dom, Adi Setia (Afkar: Jurnal Akidah dan Pemikiran Islam, 2009)
Standard, helleno-eurocentric accounts of the genesis of classical Greek rationality are increasingly being found to be problematic in the light of the classical texts themselves, comparative intellectual history and world system theory, and are hence in the process of being systemically revised. Here, a hopefully fresh contribution to the revisionist project is attempted by referring to the classical Islamic viewpoint on this question and comparing it briefly to result so far obtained in the ongoing debate between the standard and the revisionist models of the genesis of Greek rationality.